FUTURE-ORIENTED EDUCATION : REKONSTRUKSI LANDASAN PENDIDIKAN UNTUK GENERASI MASA DEPAN - Aron Rixcy Komea; Ira Shafira Kaban; Taslim Muhammad; Jhon E Bangngu Roi; Diana; Ika Pratiwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study analyzes future-oriented education with the aim of describing the reconstruction of educational foundations relevant for future generations, developing educational concepts and strategies that are adaptive to changes in digital and social technology. This research uses a literature review method by conducting an in-depth study (reading many books, journals, and research) on education in the aspects of the future, educational leadership, organizational behavior, and educational philosophy that have been previously studied. The analysis technique is carried out descriptively and analytically by collecting data, reducing data, and presenting data from various relevant sources. The results of the study indicate that a future-oriented educational approach focuses on the development of 21st-century skills, digital literacy, creativity, critical thinking, collaboration, and character and human values. Fundamental reconstruction of education is carried out by changing the curriculum, improving visionary and adaptive leadership, integrating technology into teaching, and developing an innovative and collaborative school organizational culture that is effective. On the other hand, global challenges such as the industrial revolution 4.0, society 5.0, educational disparities, and social change require an increasingly flexible and sustainable education system. The implications of this research confirm that future-oriented education is a crucial paradigm for developing a relevant, adaptive, and humane education system that prepares the next generation to effectively face global dynamics.